1999
DOI: 10.1021/jf990474l
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Ferric Iron to the Cell Walls and Membranes of Bifidobacterium thermophilum:  Effect of Free Radicals

Abstract: Bifidobacterium thermophilum (ATCC 25866) was incubated with 100-120 microM (59)FeSO(4) and 300 microM excess of H(2)O(2) for up to 120 min in the presence and absence of glucose. Samples were withdrawn after 5, 30, 60, and 120 min. These were protoplasted and (59)Fe(III) measured in the supernatant fraction (cell walls) and protoplasts (cell membranes). These experiments were also repeated in the presence of 400 microM Al(III), which, in whole cells, caused an increase in Fe(III) binding. The amount of iron i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Enterobacteriaceae are very good Fe scavengers (Andrews et al ., ), and lactobacilli do not require Fe for growth in nucleotide‐rich environments (Imbert & Blondeau, ; Elli et al ., ), which gives both bacterial groups a growth advantage during Fe‐restricted conditions. Bifidobacteria are reported to bind Fe to their cell walls and membranes, which may increase their survival during low Fe environmental conditions (Kot & Bezkorovainy, ). The clear growth advantage of bifidobacteria in a complex gut microbiota during very low Fe conditions is demonstrated by their high abundance (64.8%) during the 2,2′‐dipyridyl and Chelex ® fermentation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterobacteriaceae are very good Fe scavengers (Andrews et al ., ), and lactobacilli do not require Fe for growth in nucleotide‐rich environments (Imbert & Blondeau, ; Elli et al ., ), which gives both bacterial groups a growth advantage during Fe‐restricted conditions. Bifidobacteria are reported to bind Fe to their cell walls and membranes, which may increase their survival during low Fe environmental conditions (Kot & Bezkorovainy, ). The clear growth advantage of bifidobacteria in a complex gut microbiota during very low Fe conditions is demonstrated by their high abundance (64.8%) during the 2,2′‐dipyridyl and Chelex ® fermentation period.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae are very good Fe scavengers (Andrews et al, 2003), and lactobacilli do not require Fe for growth in nucleotide-rich environments (Imbert & Blondeau, 1998;Elli et al, 2000), which gives both bacterial groups a growth advantage during Fe-restricted conditions. Bifidobacteria are reported to bind Fe to their cell walls and membranes, which may increase their survival during low Fe environmental conditions (Kot & Bezkorovainy, 1999 The findings of this in vitro fermentation studies are very consistent with the data of a recent rat study using an Fe depletion-repletion assay to investigate the impact of Fe on gut microbiota (Dostal et al, 2012). Similar to our in vitro results, Fe deficiency in rats induced a strong decrease in butyrate and propionate production along with a decrease in butyrate-and propionate-producing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that this inhibitory effect could be largely eliminated by pretreating the organism with 100-400 mm aluminum (III). Al (III) is known to potentiate free radical effects in the plasma membrane (Kot & Bezkorovainy, 1999), leading to increased iron binding by B. thermophilum which may potentiate its probiotic action.…”
Section: Article In Pressmentioning
confidence: 99%
“…Indeed, it has been hypothesized that one of the beneficial actions of health-promoting or probiotic bacteria is to sequester iron, thus making it less available to pathogens, thus representing another form of nutritional immunity. 17 A further benefit of iron sequestration is that it would abate free radical production in the gastrointestinal tract (GIT) or at sites of inflammation, where OH-free radicals are produced by the action of neutrophils or other means. 18 Iron-induced free radical damage to DNA appears to promote the development of cancer, while cancer cells are also known to grow rapidly in response to iron.…”
Section: Introductionmentioning
confidence: 99%